Penerapan Teknologi Qr Code Berbasis Web pada Sistem Manajemen Inventaris di Gudang PT XYZ - Hery; Renaldo Luih, Joshua; Alencia Haryani, Calandra; E. Widjaja, Andree (Technomedia Journal, 2022)
At this time the use of technology is very important to support a company's business processes so that companies can gain a competitive advantage. PT Happy Bangunnusa is a company that wants to apply technology in running its business. PT Happy Bangunnusa is a company engaged in the construction sector with a focus on community development and irrigation. Currently, PT Bahagia Bangunnusa is still manually managing the goods it owns, so that it sees the risk of errors in recording the entry and exit of goods. To be able to manage the goods owned by PT Bahagia Bangunnusa, an inventory management system is needed by applying QR Code technology which can facilitate the process of collecting data on the goods owned. Therefore, the research carried out is the application of web-based QR Code technology to the inventory management system at the PT Bahagia Bangunnusa warehouse. The results of the application of web-based QR Code technology on the inventory management system at the PT Bahagia Bangunnusa warehouse can increase the effectiveness of the business processes carried out and assist in the management of goods owned by PT Bahagia Bangunnusa.